Cucurbitacins – An insight into medicinal leads from nature - Kaushik, Ujjwal; Aeri, Vidhu; Mir, Showkat R. (Pharmacognosy Reviews)
Cucurbitacins which are structurally diverse triterpenes found in the members of Cucurbitaceae and several other plant families possess immense pharmacological potential. This diverse group of compounds may prove to be important lead molecules for future research. Research focused on these unattended medicinal leads from the nature can prove to be of immense significance in generating scientifically validated data with regard to their efficacy and possible role in various diseases. This review is aimed to provide an insight into the chemical nature and medicinal potential of these compounds exploring their proposed mode of action, probable molecular targets and to have an outlook on future directions of their use as medicinal agents.
Keywords: Cucurbitaceae; cucurbitacin; triterpenoids